Information Technology Governance Assessment in Universitas Atma Jaya Yogyakarta using COBIT 5 Framework - Gabriella Sabatini; Djoko Budiyanto Setyohadi; Yohanes Sigit Purnomo W. P. (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
The use of Information Technology (IT) in education is a must now and it should bring benefits to education especially in the university level. Good information technology governance is required in the field of education from planning to implementation. This study aims to evaluate how effective and efficient the implementation of information technology governance at the Universitas Atma Jaya Yogyakarta as measured by COBIT 5 Framework.The method used is conducting a survey by distributing questionnaires to UAJY’s information system office employees and observing documents that are adjusted to the control objectives in the COBIT 5 Framework. This study uses four control objectives, namely APO (Align, Plan, and Organize), BAI (Build, Acquire, and Implement), and DSS (Monitor, Evaluate, Asses). The first stages of the study was data collection, second was analyzing maturity and gap level, third was analysing and problem finding in the implementation of IT governance and proposing recommendations, and fourth was conclusions and suggestions. The result of this research is that Universitas Atma Jaya Yogyakarta has applied the IT governance at level 3 (Established). It means that at this level the process has been built then implemented in accordance to the defined or predetermined process, and able to achieve the result of theprocess.